Workshop Ketahanan Pangan Pemberdayaan Komoditi Pisang Sebagai Olahan Brownise Pisang - Alif Achadah; Muhamad Imron; M. Wildan Hafidz; Abdurrahman Sholeh (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Real Work Lecture (KKN) is a community service activity that is packaged in academic activities under the auspices of educational institutions, in this case Higher Education (PT), both private and public. With this activity, it is hoped that the KKN participants, who in this case are students, can mix and implement the knowledge gained during the learning process at the academic bench. Another objective in the implementation of KKN is to raise student and lecturer awareness, in this case the academic community is related to problems that exist in the social environment, to participate in the development of human resources and natural resources so that they can trigger the development of social life in society. This Community Service activity in the form of KKN provides assistance in Sidodadi Village which is carried out in the form of an in-person workshop. Meetings with the target community were held to check the readiness of the target community as well as provide socialization regarding the benefits, various examples of processed banana products, as well as provide information regarding the nutritional value of bananas